Building Students’ Tolerance through Multicultural Education in Inclusive Elementary Schools - Ana Quthratun Nada; Erni Munastiwi; Zainal Arifin (Universitas Wahid Hasyim Semarang, 2025)
This study is motivated by the importance of cultivating tolerance among students in inclusive elementary schools, where regular students and students with special needs learn together. The aims of this study are to analyze the integration of multicultural education in learning practices, identify its influence on the development of students’ tolerance, and examine the role of teachers as mediators between multicultural values and tolerance practices in inclusive classrooms. This study employs a qualitative method with a library research approach, drawing data from literature on inclusive education, multicultural education, and character formation. The findings indicate that multicultural education significantly contributes to fostering respect for differences through the integration of multicultural values into instructional content, teaching methods, learning media, and school routines. Teachers play a central role in creating an inclusive learning climate and encouraging tolerant behaviors among students. This study emphasizes that teachers’ competencies and supportive inclusive education policies are crucial in ensuring the successful development of tolerance in inclusive elementary schools.